Language Comprehension of Rural Chicano and Anglo Kindergarten Children - Wesley Little; Maximiliano Contreras (Journal of Research in Rural Education, 1986)
The purpose of this study was to measure and compare the level of language comprehension of entering rural Chicano and Anglo kindergarten age children with established national norms using the Carrow Test of Auditory Comprehension of Language. Children were pre-tested and then post-tested after 20 weeks of regular classroom instruction. Results of the study indicate that both rural Chicano and rural Anglo children show growth in language comprehension as compared to national norms of children of the same nationality and socio-economic background after 20 weeks of kindergarten instruction. No significant difference in language comprehension was found between male and female children within the rural Chicano or rural Anglo groups either before or after 20 weeks of instruction. Rural Anglo children from a middle socio-economic background scored significantly higher in language comprehension than rural Chicano children of low socio-economic background both before and after 20 weeks of instruction. A random sample of 104 beginning kindergarten children (Chicano, N=43, and Anglo, N=61) was selected from different geographic regions of the state